A Case Study of Teachers use of Instructional Methods in Online Learning at Eastern Mediterranean University - Mokhtari, Leila (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Online learning that is defined as instruction delivered on a computer through the use of internet has been a part of educational revolution. Therefore, considering teaching methods, which teachers use for online courses, is very significant. Teaching methods specify the quality of instruction and it‟s important to consider which methods have already been implemented and how we as teachers can improve and change these methods in order to have a high quality and more effective online education. In this research, the researcher investigated the existing teaching methods for two online courses which are Banking and Finance Master‟s program and Hotel Management Master‟s program. The purpose of this research is to promote online programs in EMU by altering the existing teaching methods.

ÖZ: E-öğrenme, bir bilgisayarda internet yolu ile verilen öğretim olarak tanımlanmıştır ve eğitim devriminin bir parçası olmuştur. Öğretmenlerin E-öğrenme kursları için kullandığı öğretim yöntemlerini göz önüne almak çok önemlidir. Öğretim yöntemleri, eğitim kalitesinin göstergesidir. Hangi yöntemlerin uygulandığını ve bu yöntemlerin nasıl geliştirilebileceği ve değiştirileceği de yüksek kaliteli E-öğrenmeye ve etkili eğitim için önemlidir. Bu araştırmada, araştırmacı EMU'daki var olan E-öğrenme programlarının ne derece etkin ve verimli kullanıldığını araştırmıştır. Araştırma, Bankacılık ve Finans Yüksek Lisans programı ve Otelcilik Yüksek Lisans Programlarında uygulanmıştır. Bu araştırmanın amacı, öğretmenlerin DAÜ'de E-öğrenme üzerinde ki var olan öğretim yöntemlerini geliştirmeleri veya yeni bir model önerisinde bulunmaktır.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2017. Supervisor: Assist. Prof. Dr. Bengi Sonyel.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies in Education--Online Learning--Eastern Mediterranean University; Education - Computer network resources--E-Learning; Mobile communication systems in education; Schools--Teaching, Aids and Devices; Educational Technology--Educational Media--E-Learning; Teaching Aids--Teaching Materials--Teaching Equipments--Instructional materials; Teaching - Computer network resources; Online learning; Effective teaching methods; Effective teaching; Teaching programs; Reflection